Advanced Topics in Information Retrieval - Melucci, Massimo; Baeza-Yates, Ricardo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
Information retrieval is the science concerned with the effective and efficient retrieval of documents starting from their semantic content. It is employed to fulfill some information need from a large number of digital documents. Given the ever-growing amount of documents available and the heterogeneous data structures used for storage, information retrieval has recently faced and tackled novel applications. In this book, Melucci and Baeza-Yates present a wide-spectrum illustration of recent research results in advanced areas related to information retrieval. Readers will find chapters on e.g. aggregated search, digital advertising, digital libraries, discovery of spam and opinions, information retrieval in context, multimedia resource discovery, quantum mechanics applied to information retrieval, scalability challenges in web search engines, and interactive information retrieval evaluation. All chapters are written by well-known researchers, are completely self-contained and comprehensive, and are complemented by an integrated bibliography and subject index. With this selection, the editors provide the most up-to-date survey of topics usually not addressed in depth in traditional (text)books on information retrieval. The presentation is intended for a wide audience of people interested in information retrieval: undergraduate and graduate students, post-doctoral researchers, lecturers, and industrial researchers.
Digital Libraries -- Scalability Challenges in Web Search Engines -- Spam, Opinions, and other Relationships: Towards a Comprehensive View of Web -- The User in Interactive Information Retrieval Evaluation -- Aggregated Search -- Quantum Mechanics and Information Retrieval -- Multimedia Resource Discovery -- Information Retrieval in Context -- Digital Advertising: An Information Scientist's Perspective.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Computer Science; Information Storage and Retrieval; Information Systems Applications (incl.Internet).